2022
DOI: 10.1111/bjop.12557
|View full text |Cite
|
Sign up to set email alerts
|

Are brand names special words? Letter visual‐similarity affects the identification of brand names, but not common words

Abstract: Brand names are often considered a special type of words of special relevance to examine the role of visual codes during reading: unlike common words, brand names are typically presented with the same letter‐case configuration (e.g., IKEA, adidas). Recently, Pathak et al. (European Journal of Marketing, 2019, 53, 2109) found an effect of visual similarity for misspelled brand names when the participants had to decide whether the brand name was spelled correctly or not (e.g., tacebook [baseword: facebook] was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 76 publications
2
12
0
2
Order By: Relevance
“…Critically, these models assume that abstract letter identities are equally confusable with each other. Consistent with this tenet, prior lexical decision studies have shown that both accuracy and response times to pseudowords created by replacing a single letter from a baseword are remarkably alike regardless of whether the replacement involves a similar letter (e.g., viotin [baseword: violin]) or a different letter (e.g., viocin ) in both skilled readers and developing readers ( Perea & Panadero, 2014 ; see also Perea, Baciero, et al, 2022 , and Gutierrez-Sigut et al, 2022 , for converging behavioural and electrophysiological evidence, respectively). Clearly, if visual, non-abstract elements had played a relevant role during word recognition, it would have been more difficult to reject viotin as a word than viocin .…”
Section: Orthographic Processing In Visual Formatmentioning
confidence: 67%
See 2 more Smart Citations
“…Critically, these models assume that abstract letter identities are equally confusable with each other. Consistent with this tenet, prior lexical decision studies have shown that both accuracy and response times to pseudowords created by replacing a single letter from a baseword are remarkably alike regardless of whether the replacement involves a similar letter (e.g., viotin [baseword: violin]) or a different letter (e.g., viocin ) in both skilled readers and developing readers ( Perea & Panadero, 2014 ; see also Perea, Baciero, et al, 2022 , and Gutierrez-Sigut et al, 2022 , for converging behavioural and electrophysiological evidence, respectively). Clearly, if visual, non-abstract elements had played a relevant role during word recognition, it would have been more difficult to reject viotin as a word than viocin .…”
Section: Orthographic Processing In Visual Formatmentioning
confidence: 67%
“… Pathak et al (2019) found that misspelled logotypes like anazon (original logo: amazon ) produced more errors and longer latencies than misspelled logotypes like atazon —note that n is more visually similar than t to the m in a m azon. Perea, Baciero, et al (2022) replicated this finding using another set of logotypes; critically, they found no evidence of a letter-similarity effect in parallel experiments with misspelled common words (e.g., amarillo [yellow in Spanish]; anarillo = atarillo ). They argued that logos, being typically presented in a single typeface and design, were more susceptible to the effects of perceptual factors than common words.…”
Section: Orthographic Processing In Visual Formatmentioning
confidence: 69%
See 1 more Smart Citation
“…Regarding the most recent works by the authors who receive the most citations, some of them, including Rickheit [ 107 ], Herrmann [ 122 ], and Brysbaert [ 91 ], address general topics such as the history of psycholinguistics [ 107 ], language use [ 122 ], reading [ 123 ], and individual differences [ 124 , 125 ]. Other authors, such as Levelt [ 3 ], address more specific topics, including visual word recognition [ 126 ], semantic frames [ 127 ], bilingualism [ 128 ], and grammar learning [ 129 ].…”
Section: Discussionmentioning
confidence: 99%
“…They claimed that this boost in the size of the transposed-letter effect for misspelled logotypes was due to the inherent characteristics of logotypes: logotypes are typically consistent across contexts, featuring a speci c and recognizable letter case, typeface, and color combination. Perea et al 13,14 proposed that during the processing of logotypes, readers encode abstract orthographic information (i.e., letter identity and order) and information arising from the graphical design of the brand name.…”
Section: Introductionmentioning
confidence: 99%